The impact of simulation practice on student nurses’ skills: the case of integrated newborn and childhood illness management at the university of Namibia - Iita, Hermine; Neshuku, Hanna; Chirimbana, Moses (International Journal of Advanced Nursing Studies, 2016)
The purpose of this study was to determine if guided simulation practice could enhance practical skills of student nurses in management of childhood illnesses, based on the Integrated Management of Newborn and Childhood Illness (IMNCI) approach.The objective was to determine the level at which guided classroom simulation practice enhances the skills of student nurses regarding assessment and classification of sick children aged two months to five years for treatment. A quantitative research approach using a pre-test and post- test strategy was used. Descriptive statistics were done and a t-test was also performed to determine the difference in the means. Findings demonstrate that there is an improvement in the performance of student nurses as a result of the guided classroom simulation practice. Recommendations include that student nurses be exposed to guided simulation practice before they are deployed in the clinical area for the actual assessment and classification of sick children based on the Integrated Management of Neonatal and Childhood Illness.